Contribution of Perceived Social Support (Peer, Family, and Teacher) to Academic Resilience during COVID-19 - Permatasari, Nirwana; Rahmatillah Ashari , Farhana; Ismail, Nursyamsu (Golden Ratio of Social Science and Education, 2021)
The purpose of this study is analyzed and reconfirm each item on perceived social support e.g., peers, families, and teachers on academic resilience based on online learning during COVID-19. This study uses a quantitative approach with a correlational design as a method. The sample in this study consisted of 291 cadets at Politeknik Ilmu Pelayaran (Marine Science Polytechnic) in Makassar city selected through accidental sampling. Data were analyzed using linear regression analysis with SPSS as a statistical tool. The result of this study indicates perceived social support significantly contributes to academic resilience at 71.8% (R2 = 0.718; Sig < 0.01), and 28.2% comes from outside of the study variables. Every aspect of perceived social support contributes to academic resilience. The contribution of family support by 42.4; teacher support by 16.6%, and peer support by 12.8%. The findings in the study show that family support is the support element that dominant contributes for students in the online learning during the process and gives the highest contribution to academic resilience in the online learning process. Therefore, individuals' perception of peers, family, and teachers who can provide assistance, support, and care when students experience difficulties in the academic field can increase academic resilience.